Exploring the Economic Value of Ecotourism: A Case Study of the Lekki Conservation Center in Lagos, Nigeria Using the Travel Cost Method - Falabi M.O; Odetoye, A.S; Olabamowo O.E (CV. Literasi Indonesia, 2024)
This study aimed to explore the travel behavior of visitors to the Lekki Conservation Centre (LCC) in Lagos, Nigeria. The study employed a survey research design, and data was collected from 200 visitors to the LCC using a structured questionnaire. The questionnaire contained questions on the visitors' demographic information, travel characteristics, means of transportation, duration of stay, and money spent at the recreational center. The results showed that the majority of visitors to the LCC were young adults, with a mean age of 28 years. Visitors primarily traveled to the recreational site using private vehicles, with public service vehicles and motorcycles also being commonly used means of transportation. The study found that the average cost of travel to the LCC was N2,175.00, with visitors spending an average of N30,000.00 while at the recreational center. The study concluded that the LCC is a popular recreational site in Lagos, attracting visitors from different parts of the city. It recommended that the management of the LCC improve the facilities at the center to enhance visitors' experiences. The study also suggested that the Lagos State Government should invest in the development of other recreational centers across the city to reduce the pressure on the LCC and provide more options for residents and visitors to explore.